Volatile-Based Short-Term Sedation in Cardiac Surgical Patients. Issue 5 (May 2015) - Jerath, Angela; Beattie, Scott W.; Chandy, Tony; Karski, Jacek; Djaiani, George; Rao, Vivek; Yau, Terrence; Wasowicz, Marcin
<x xml:space="preserve">Abstract</x> Objective: To evaluate the differences in extubation times in a group of cardiac surgical patients who were anesthetized and sedated with either IV propofol or inhaled volatile anesthetic agents. Design: This was a prospective randomized controlled trial performed between September 2009 and August 2011. Setting: Cardiovascular ICU within a tertiary referral university-affiliated teaching hospital. Patients: One hundred forty-one patients undergoing coronary artery bypass graft surgery with normal or mildly reduced left ventricular systolic function. Intervention: Participants were randomly assigned to receive anesthesia and postoperative sedation using IV propofol (n = 74) or inhaled volatile (isoflurane or sevoflurane) anesthetic agent (n = 67). Measurements and Main Results: Patients sedated using inhaled volatile agent displayed faster readiness to extubation time at 135 minutes (95–200 min) compared with those receiving IV propofol at 215 minutes (150–280 min) (p < 0.001). Extubation times were faster within the volatile group at 182 minutes (140–255 min) in comparison with propofol group at 291 minutes (210–420 min) (p < 0.001). The volatile group showed a higher prevalence of vasodilatation with hypotension and higher cardiac outputs necessitating greater use of vasoconstrictors. There was no difference in postoperative pain scores, opioid consumption, sedation score, ICU or hospital length of stay, or patient mortality. Conclusions: Inhaled volatile anesthesia and sedation facilitates faster extubation times in comparison with IV propofol for patient undergoing coronary artery bypass graft surgery.